2002
DOI: 10.1097/00004770-200203000-00001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Current and Potential Dental Etchants on Nerve Compound Action Potentials

Abstract: In this study, a 35% phosphoric acid gel (3M Scotchbond etchant), a nonrinse etchant (NRC), and two EDTA-containing conditioners (RC-Prep and File-Eze) were tested in vitro for blocking nerve conductance evoked in the rat sciatic nerve after local application. The phosphoric acid gel and NRC completely and irreversibly inhibited conductance. On the other hand, RC-Prep reduced the compound action potentials (cAPs) by 50% in 120 min. With File-Eze, the reduction in cAPs was less than 50% after an application tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 4 publications
1
19
0
Order By: Relevance
“…The bath contained Tyrode solution (8 g/l NaCl, 0.2 g/l KCl, 0.2 g/l CaCl 2 , 0.1 g/l MgCl 2 , 1 g/l NaHCO 3 , 0.05 g/l NaH 2 PO 4 , 1 g/l glucose) continuously gassed with O 2 and CO 2 (95% and 5%, respectively). 27,30,31 The pH was 7.4 and the temperature was kept constant at 37°C throughout the experiments. The nerves were continuously perfused with Tyrode solution at a rate of 2 ml/min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bath contained Tyrode solution (8 g/l NaCl, 0.2 g/l KCl, 0.2 g/l CaCl 2 , 0.1 g/l MgCl 2 , 1 g/l NaHCO 3 , 0.05 g/l NaH 2 PO 4 , 1 g/l glucose) continuously gassed with O 2 and CO 2 (95% and 5%, respectively). 27,30,31 The pH was 7.4 and the temperature was kept constant at 37°C throughout the experiments. The nerves were continuously perfused with Tyrode solution at a rate of 2 ml/min at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…27,30,31 During all experiments, the percentage amplitude of the cAPs versus time diagram was plotted. 27,30,31 Machined/turned-surface commercially-pure titanium (cpTi) implants (Nobelbiocare, Göteborg, Sweden), TiO 2 -blasted cpTi implants (Astra Tech, Mölndal, Sweden), and SLA-surface cpTi implants (ITI, Straumann Institute, Waldenburg, Switzerland) were used in this study. Each group consisted of three implants, and were tested on sciatic nerves obtained from a total of nine animals [Figures 2(a) and 2(b)].…”
Section: Methodsmentioning
confidence: 99%
“…Since one major reason for the use of etchants in the total etch procedure is to open up dentin tubules which have been previously occluded by the smear layer, the ability of the etchant to modify or block the nerve transmission could be considered a valuable compensation for the hydrodynamic forces it will allow to occur. However, in a recent study which showed neurotoxic potential of strong dentin conditioners such as 35% phosphoric acid [19], it was speculated that the acid would presumably not be able to alter the composition of the dentinal fluid in a single application, especially when applied to intact dentin which is a relatively indirect access to the pulpal nerves. Thus, the authors concluded that the time-course of the blocking effect in clinical use may be longer than that achieved within the limitations of their study, since there seems to be no way dentin conditioners could be titrated or applied in such a way as to just balance these two opposite effects to reach the desired clinical result [19].…”
Section: Resultsmentioning
confidence: 99%
“…However, in a recent study which showed neurotoxic potential of strong dentin conditioners such as 35% phosphoric acid [19], it was speculated that the acid would presumably not be able to alter the composition of the dentinal fluid in a single application, especially when applied to intact dentin which is a relatively indirect access to the pulpal nerves. Thus, the authors concluded that the time-course of the blocking effect in clinical use may be longer than that achieved within the limitations of their study, since there seems to be no way dentin conditioners could be titrated or applied in such a way as to just balance these two opposite effects to reach the desired clinical result [19]. Based on this discussion, it does not seem that there is a way in which the relatively weaker acids in FL Bond, SE Bond and Mac Bond could have contributed to the rapid inhibiton of the CAPs in the present study [8].…”
Section: Resultsmentioning
confidence: 99%
“…During all experiments, the percentage amplitude of the cAPs versus time diagram was plotted. 8,[10][11] After the completion of each experiment, the tested nerve was discarded and a fresh nerve was used for the upcoming experiment. The first set of 6 sciatic nerves was used for control group and tested for 100 min at 10 min intervals.…”
Section: Methodsmentioning
confidence: 99%